The urgent need to improve the tools to assess clinical benefit and value of cancer treatment. (September 2017) - Sobrero, Alberto; Puccini, Alberto; Bregni, Giacomo; Bruzzi, Paolo
Abstract: There are several controversies in the assessment of the benefit, value and sustainability of cancer drugs. First, there is a surprising disagreement on the impact of drugs on the overall outcome of cancer treatment. Second, raising the bar of efficacy in clinical trials is claimed by many, but at the same time, being conservative appears justified as well, given the overall benefit of multiple incremental gains, typically observed in advanced solid tumours. Third, sustainability of cancer drug cost is a prohibitive challenge, but no major successful action has been taken so far. The reason for these controversies can be understood using concepts borrowed from psychological and cognitive sciences: each stakeholder has different perspectives generated by different availability biases; this implies different priorities, leading people to think, choose and act differently. Providing an 'objective' assessment of the benefit and value of a cancer drug makes sense only if the perspective adopted is clearly identified. The American Society of Clinical Oncology (ASCO) scale fits the patients' perspective by helping individual patients to choose the most valuable therapeutic option for their condition. Conversely, the European Society for Medical Oncology (ESMO) scale has a public health perspective: ranking the clinical benefit of oncologic drugs to identify those agents that should be available in every EU country. Because this scale is being adopted for reimbursement purposes in several European regions, the current major methodological problems of the scale should urgently be corrected to avoid unwanted societal consequences. Highlights: Obtaining an objective assessment of clinical benefit satisfying all stakeholders is unrealistic. Three major perspectives (patients, doctors and public health) can be identified. The ASCO framework of clinical benefit takes the patients perspective. The ESMO scale takes a public heath perspective. The ESMO scale must therefore be optimised before its use for reimbursement purposes.